The Efficacy of Fuller Approach on the Reading Performance of the Grade 7 Students of Villa Kananga Integrated School - Mallo, Charrie Mae T.; Cuizon, Marivic B. (Randwick International of Education and Linguistics Science Journal, 2025)
This study assessed the efficacy of the Fuller Approach—a structured reading intervention combining phonics, alphabet recognition, and whole-word recognition—on the reading performance of Grade 7 students at Villa Kananga Integrated School, Butuan City. Using a one-group pre-experimental design, the research measured students’ reading skills before and after the intervention. The Philippine Informal Reading Inventory (Phil-IRI) served as the primary tool for data collection, evaluating word recognition, reading speed, and comprehension. Results revealed a significant improvement in reading performance, as evidenced by increased posttest scores in all areas: word recognition, reading comprehension, words Correct Per Minute (WCPM), and error rate reduction. A paired sample t-test confirmed the statistical significance of the observed gains (p<0.001). Theoretical frameworks such as Schema Theory and Vygotsky’s Sociocultural Theory supported the study, highlighting the importance of prior knowledge, scaffolding, and socially mediated learning. The findings affirm that the Fuller Approach is a highly effective method for enhancing reading fluency and comprehension among struggling readers. The study recommends continued application of this approach, enhanced teacher training, and the integration of individualized interventions to sustain student reading gains.